Human Pluripotent Stem Cell‐Derived Radial Glia Recapitulate Developmental Events and Provide Real‐Time Access to Cortical Neurons and Astrocytes. (1st April 2015) - Duan, Lishu; Peng, Chian-Yu; Pan, Liuliu; Kessler, John A.
Abstract : Studies of human cerebral cortex development are limited by difficulties in accessing and manipulating human neural tissue at specific development stages. We have derived human radial glia (hRG), which are responsible for most cerebral cortex neurogenesis, from human pluripotent stem cells. These hRG display the hallmark morphological, cellular, and molecular features of radial glia in vitro. They can be passaged and generate layer‐specific subtypes of cortical neurons in a temporal and passage‐dependent fashion. In later passages, they adopt a distinct progenitor phenotype that gives rise to cortical astrocytes and GABAergic interneurons. These hRG are also capable of following developmental cues to engraft, differentiate, migrate, and integrate into the embryonic mouse cortex when injected into E14 lateral ventricles. Moreover, hRG‐derived cells can be cryopreserved at specific stages and retain their stage‐specific phenotypes and competence when revived. Our study demonstrates that cultured hRG maintain a cell‐intrinsic clock that regulates the progressive generation of stage‐specific neuronal and glial subtypes. It also describes an easily accessible cell source for studying hRG lineage specification and progression and an on‐demand supply of specific cortical neuron subtypes and astrocytes. Abstract : A protocol was successfully developed that generates developmentally accurate radial glia from human pluripotent stem cells. Such cultures can be passaged and frozen and demonstrate passage‐wise sequential generation of cortical neuron subtypes, cortical astrocytes, and interneurons. A late progenitor stage has also been characterized that has the capacity to generate large numbers of cortical astrocytes and dorsal‐derived cortical interneurons.